Design of an integrated 60 GHz cross-coupled oscillator in SiGe technology - Agethen, Roman; Lämmle, Benjamin; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE Semiconductor Conference Dresden, 2011)
This paper presents the design of an integrated fully differential 60GHz voltage controlled oscillator in SiGe technology featuring f t = 200 GHz high speed bipolar HBTs. The VCO is based on a differential Colpitts VCO. The core consumes an average amount of 26mA @ 3.3V supply voltage. The tuning bandwidth is about 12%. The utilized buffer at the output consumes additional 64 mA @ 3.3V and provides an output power of 13dBm over the tuning bandwidth. The phase noise @ 1MHz is less than -75 dBc/Hz.
elib2cris::1512001600,agethen2011a